Analysis of student’s achievement motivation in learning chemistry - Beta Wulan Febriana (Universitas Sebelas Maret, 2017)
The aim of the study is to determine the effect of student’s achievement motivation toward learning chemistry. This research was conducted at SMK Kesehatan Rahani Husada. The descriptive method was used in this research. The data was collected using test for student’s cognitive achievement and questionnaire for achievement motivation. Data was analyzed using descriptive analysis techniques. The results show that achievement motivation on XI grade of SMK Kesehatan Rahani Husada students was in the category of achievement motivation “high” at 47,54%. Moreover, achievement motivation tends effect is random to student’s achievement.